Racial discrimination and posttraumatic stress: examining emotion dysregulation as a mediator in an African American community sample. Issue 1 (31st December 2020) - Mekawi, Yara; Watson-Singleton, Natalie N.; Kuzyk, Eva; Dixon, H. Drew; Carter, Sierra; Bradley-Davino, Bekh; Fani, Negar; Michopoulos, Vasiliki; Powers, Abigail
ABSTRACT: Background : African Americans experience more severe and chronic posttraumatic stress disorder (PTSD) symptoms compared to other racial groups, and thus it is important to examine factors that are relevant for the aetiology of PTSD in this population. Although racial discrimination has been implicated as an exacerbating factor in the development and maintenance of PTSD, relatively less is known about mechanisms through which this process may occur. Objective : The purpose of this study was to examine one such mechanism, emotion dysregulation, in two independent samples of African American adults. Method : Trauma-exposed participants were recruited in a large, urban community hospital setting (initial sample n = 1, 841; replication sample n = 294). In the initial sample, participants completed a unidimensional measure of emotion dysregulation and self-reported PTSD symptoms based on the DSM-IV. In the replication sample, participants completed a multidimensional measure of emotion dysregulation and a diagnostic interview of PTSD symptoms based on the DSM-5. Mediation analyses were used to test our hypotheses. Results : Across both samples, results indicated that racial discrimination was indirectly associated with PTSD symptoms through emotion dysregulation (even when trauma load was added as a covariate). Conclusions : Taken together, these results provide strong evidence that the association between racial discrimination and PTSD symptoms may be partially explained by the association between racial discrimination and worse emotion dysregulation. These findings elucidate the impact of racist incidents on mental health and identify modifiable emotion regulatory processes that can be intervened upon to enhance the psychological and social wellbeing of African Americans. Abstract : HIGHLIGHTS: Experiencing more racial discrimination may negatively impact how African Americans are able to regulate emotions; Difficulty regulating emotions may partly explain the link between racial discrimination and PTSD symptoms among African Americans.